Village Community Empowerment Support Against West Bali National Park Hall, Jembrana Regency - Luh Putu Sudini; Desak Gde Dwi Arini; Ni Made Widya Pratiwi; Agus Ngurah Krisna Kepakisan; Anak Agung Nia Listiari; I Komang Adhi trisna Saputra (Community Service Journal of Law, 2022)
West Bali National Park, Jembrana Regency is a nature conservation area that has native ecosystems, managed with a zoning system that is used for research, scientific, educational purposes, to support cultivation, tourism and recreation. West Bali National Park, Jembrana Regency is the only national park in Bali Province. Local wisdom is one of the things that must be considered in Environmental Protection and Management activities, especially in community activities to preserve the protected forest of the West Bali National Park. Partner Issues: 1) Lack of optimization of local wisdom towards the West Bali National Park in Supporting Village, especially Melaya Village, 2) There is no synchronization of the rights and obligations of the parties to the Conservation contract between the Village community and the Village Head, especially the Melaya Village. The research method used is empirical legal research, namely by primary data collection through observation, interviews, and distributing questionnaires. After the primary data has been collected, it is processed, using qualitative methods and analyzed using Descriptive analytical techniques to get conclusions with accurate data. The output targets of this service are: To form a draft conservation contract between the Village of Support (Desa Melaya) and the West Bali National Park Center, a reputable accredited Service Journal (Community journal of Law) and the Sutramas Journal, HKI, Print Media.